Annual report of the Committee on Gynecologic Oncology, the Japan Society of Obstetrics and Gynecology: Annual patient report for 2017 and annual treatment report for 2012. Issue 5 (25th February 2021) - Nagase, Satoru; Ohta, Tsuyoshi; Takahashi, Fumiaki; Yaegashi, Nobuo
Abstract: Aim: To provide information including the trend of gynecological malignancies in Japan, we hereby present the Annual Patient Report for 2017 and the Annual Treatment Report for 2012, on the outcomes of patients who started treatment in 2012. Methods: The Japan Society of Obstetrics and Gynecology maintains an annual tumor registry, where information on gynecological malignancies from various participating institutions is gathered. The data of patients whose treatment with gynecologic malignancies was initiated in 2017 were analyzed retrospectively. Survival of the patients who started treatment with cervical, endometrial and ovarian cancer in 2012 was analyzed by using the Kaplan‐Meier, log‐rank and Wilcoxon tests. Results: Treatment was initiated in 2017 for 7710 patients with cervical cancer; 11 120 with endometrial cancer; 7029 with ovarian, tubal and peritoneal cancer; 2164 with ovarian borderline tumors; and with the others (213 vulvar cancer, 139 vaginal cancer, 366 uterine sarcoma, 41 uterine adenosarcoma and 131 trophoblastic diseases). This clinicopathological information was summarized as the patient annual report. The 5‐year survival rates of the patients with cervical cancer were 92.9, 75.5, 58.2 and 26.7% for stages I, II, III and IV, respectively. The 5‐year survival rates for the patients with endometrial cancer were 93.6, 85.6, 72.6 and 27.3% for stages I, II, III and IV, respectively. The 5‐year survival rates for the patients with ovarian cancer (surface epithelial‐stromal tumors) were 92.5, 83.5, 49.5 and 30.8% for stages I, II, III and IV, respectively. Conclusion: The annual tumor report is an important survey that provides knowledge on gynecological malignancy trends in Japan.